2014
DOI: 10.4238/2014.january.31.4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of upland cotton (Gossypium hirsutum) cultivars developed in Hubei Province by mapped SSRs

Abstract: ABSTRACT. The genetic diversity of 51 upland cotton cultivars with different parental origins and breeding periods that were developed in Hubei Province was studied on the basis of 237 mapped simple sequence repeat markers covering the cotton genome. A total of 108 polymorphic primer pairs amplified 196 loci; the polymorphism information content range was 0.04 to 0.83, with an average of 0.46. A model-based clustering analysis (STRUCTURE) of the genomic data identified 3 clear subpopulations, and the result wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Range (0.126-0.693) and average (0.485) of PIC showed that the panel of markers used in the present study was sufficient to explore the genetic variation among the genotypes of the present study. PIC value was in agreement with the results of Tu et al (2014) (0.46), Wang et al (2016) (0.47), andDong C. G. et al (2018) (0.48). All 97 polymorphic markers were distributed over 26 chromosomes with an average of 3.73 markers per chromosome.…”
Section: Molecular Diversitysupporting
confidence: 91%
“…Range (0.126-0.693) and average (0.485) of PIC showed that the panel of markers used in the present study was sufficient to explore the genetic variation among the genotypes of the present study. PIC value was in agreement with the results of Tu et al (2014) (0.46), Wang et al (2016) (0.47), andDong C. G. et al (2018) (0.48). All 97 polymorphic markers were distributed over 26 chromosomes with an average of 3.73 markers per chromosome.…”
Section: Molecular Diversitysupporting
confidence: 91%
“…The average PIC value obtained in our investigation aligns with the findings of De MagalhãesBertini et al (2006), who reported a value of 0.48 while examining the genetic relationship between multiple Brazilian cotton genotypes employing SSR markers. However, our PIC value findings were greater than the value of 0.46 reported byTu et al (2014), evaluating the genetic relationship of multiple upland cotton varieties exploiting SSR markers. Correspondingly, the genetic diversity assessment conducted by Guang and Xiong-Ming, 2006 using SSR markers on various upland cotton genotypes from diverse ecological areas in China yielded a lower value of 0.62 Zhang et al (2011).…”
contrasting
confidence: 97%
“…AMOVA result showed higher genetic variance among populations. Tu et al (2014) found lower genetic variance among populations in 51 Upland cotton cultivars. The relatively higher variance among populations and lower within populations we obtained could be due to the semi-wild nature of the accessions (Keneni et al 2012).…”
Section: Discussionmentioning
confidence: 81%